Service Quality Relationship With Customer Satisfaction In Pdam - Achmad Daengs GS; Sugiharto Sugiharto; Dwi Prasetyo; Enny Istanti; Bambang Karnain (Pusat Riset dan Inovasi Nasional, 2023)
PDAM Surabaya is a company engaged in the field of clean water supply services. One of the goals in the form of PDAM is to meet the community's need for clean water, including the provision, development of facilities and infrastructure services and the distribution of clean water, while another goal is to participate in developing the economy to support regional development by expanding employment opportunities, and seeking profit as the main source. regional financing.PDAM Surabaya as one of the BUMDs is expected to be able to provide adequate marketing. Only companies that have advantages at the global level are able to satisfy and meet consumer needs and are able to produce quality products and are cost effective (Mulyadi, 2001). In order to achieve excellent marketing services, companies are faced with. The determination of the marketing strategy will serve as the basis and framework for realizing the work targets determined by management. Therefore we need a tool to determine the marketing strategy so that it can be seen to what extent the strategy and what has been determined can be achieved. Assessment of marketing targets plays an important role in the business world, due to the evaluation of the marketing strategy can be seen the effectiveness and determination of a strategy and its application within a certain time. The marketing strategy can approach the weaknesses and deficiencies that are still present in the company, for further improvements to be made in the future.